Efeito do resveratrol e da vitamina E frente a prejuízos reprodutivos causados pelo uso de ácido valpróico em ratos machos - Ourique, Giovana de Moraes (2016)
Long-term treatment with valproic acid (VPA) has been associated with adverse effects on the male reproductive function mediated by increased testicular oxidative stress. Thus, this study evaluated the potential protective effect of resveratrol (RSV 10 mg/kg, ip) and vitamin E (50 mg/kg, ip) in sperm quality and oxidative stress parameters in the testis and epididymidis of Wistar rats treated with VPA (400 mg/kg, orally) for 28 days. VPA treatment was associated with decreased sperm motility, increased oxidative damage and decreased antioxidant capacity in testis and epididymidis. RSV and vitamin E were able to prevent oxidative damage and rescue antioxidant capacity of the testis and epididymidis, preventing the impairment of sperm motility induced by VPA. These data suggest the administration of RSV or vitamin E as a therapeutic strategy to preserve sperm motility and testicular function in male patients requiring long-term treatment with VPA. Moreover, this study also evaluated the effect of VPA (1 uM, 10 uM, 100 uM, 1 mM and 3 mM) in isolated pachytene spermatocytes and round spermatids. Our results demonstrated that, in vitro, at our experimental conditions, VPA treatment induced oxidative stress and hyperacetylation of histone H4, without causing DNA damage in pachytene spermatocytes and round spermatids.